THE AUSAID (AUSTRALIAN AGENCY FOR INTERNATIONAL DEVELOPMENT) ASSISTANCE ON ENVIRONMENTAL PROGRAM IN INDONESIA IN THE CONTEXT OF MDGs (MILLENNIUM DEVELOPMENT GOALS) PROJECT ACCELERATION - Nafirotul Karima (2013)
This research tried to explore about the reason why AusAID prioritizes Indonesia to be their recipient related to the environmental program. Nowadays the environmental phenomenon has the special relation to the development. International economic relations raises special problem for environmental management especially in the developing countries. However Indonesia is home to the third largest area of tropical forest in the world, but also ranks among the highest for deforestation, forest degrada